The connection between robust legal instruments and the exceptional performance of the Islamic banking industry - Hassan, Rusni; Triyanta, Agus (Virtus Interpress, 2024)
This study investigates the pivotal role of robust legal instruments in driving the outstanding performance of Malaysia’s Islamic banking industry. Our primary objective is to discern the correlation between the regulatory framework’s legal strength and the industry’s achievements. To achieve this, we embark on a comprehensive exploration of the historical progression of Islamic banking in Malaysia. We scrutinize the dynamics and milestones that have shaped the industry, with particular emphasis on its impressive growth. We then delve into the development of the regulatory frameworks, analyzing how the availability of strong legal instruments has contributed to the sector’s triumph. This study finding the presence of robust legal instruments has been a catalyst for the ascension of Malaysia’s Islamic banking industry. Coupled with accommodating regulations and responsive regulatory institutions, these legal foundations have underpinned the sector’s remarkable success. This study underscores the critical importance of having sufficient legal instruments to nurture the Islamic banking industry. We recommend that governments aspiring to bolster Islamic banking’s performance consider the provision of such legal frameworks. Consequently, this research carries significant implications for policymakers and industry stakeholders alike, offering insights into the essential ingredients for fostering a thriving Islamic banking sector.